1997
DOI: 10.1038/sj.onc.1201323
|View full text |Cite
|
Sign up to set email alerts
|

The E1B 19K protein associates with lamins in vivo and its proper localization is required for inhibition of apoptosis

Abstract: Expression of the E1B 19K protein is required to inhibit apoptosis induced by E1A during adenovirus infection and transformation. E1B 19K is homologous to Bcl-2 in function and the two proteins also share limited amino acid sequence homology. Consequently, the E1B 19K and Bcl-2 proteins bind to and inhibit the cellular deathinducing proteins Bax, Bak and Nbk/Bik. Both E1B 19K and Bcl-2 localize to membranes of the nucleus and the endoplasmic reticulum. In addition to membrane association, and unlike Bcl-2, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…We identified BAX, 24 a protein that had been identified as a proapoptotic BCL-2 interacting protein in the Korsmeyer laboratory 25 ; natural born killer/BCL-2-interacting killer/BIKlike killer (NBK/BIK/BLK), a proapoptotic protein and the first BH3-only protein to be identified 26 ; and lamin A, which is involved in localization of E1B 19K to the nuclear envelope. 27 Other groups identified proapoptotic BAK as an E1B 19K and BCL-2 interacting protein [28][29][30] and there are a number of other joint E1B 19K/BCL-2 interacting proteins that remain poorly characterized. 31 These and other findings revealed that the BCL-2 family of proteins consists of proapoptotic and antiapoptotic members that are regulated by functional antagonism through protein-protein interactions.…”
Section: Discussion E1b 19k Blocks Apoptosis By Binding To and Inhibimentioning
confidence: 99%
“…We identified BAX, 24 a protein that had been identified as a proapoptotic BCL-2 interacting protein in the Korsmeyer laboratory 25 ; natural born killer/BCL-2-interacting killer/BIKlike killer (NBK/BIK/BLK), a proapoptotic protein and the first BH3-only protein to be identified 26 ; and lamin A, which is involved in localization of E1B 19K to the nuclear envelope. 27 Other groups identified proapoptotic BAK as an E1B 19K and BCL-2 interacting protein [28][29][30] and there are a number of other joint E1B 19K/BCL-2 interacting proteins that remain poorly characterized. 31 These and other findings revealed that the BCL-2 family of proteins consists of proapoptotic and antiapoptotic members that are regulated by functional antagonism through protein-protein interactions.…”
Section: Discussion E1b 19k Blocks Apoptosis By Binding To and Inhibimentioning
confidence: 99%
“…Mutations that cause mislocalization of the lamins, and thus change the localization of E1B 19K protein, lead to abrogation of the E1B 19K anti-apoptotic activity. 41 A possible mechanism E1B 19K may use to block apoptosis may involve sequestration of pro-apoptotic proteins. The E1B 19K protein has been shown to sequester CED-4, the C. elegans APAF-1 homologue, from the cytosol to the nucleus, abrogating the ability of CED-4 to activate caspase-8.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Bcl-2, Bcl-X L , Bax, and the Epstein ± Barr virus gene product BHRF tend to be particularly abundant in the outer mitochondrial membrane (Cory, 1995;Gonzalez-Garcia et al, 1994;Krajewski et al, 1993;Reed, 1994;Riparbelli et al, 1995;Yang and Korsmeyer, 1996;Zha et al, 1996a). In contrast, E1B19K, which lacks a TM domain, is mostly localized in the nuclear envelope (Rao et al, 1997). It appears unlikely that mere TM-lipid interactions determine the subcellular localization of these proteins.…”
Section: Predominant Localization To Intracellular Membranesmentioning
confidence: 99%
“…It appears unlikely that mere TM-lipid interactions determine the subcellular localization of these proteins. The preferential localization of E1B19K may be dictated by protein-protein interactions with nuclear lamins A/C (Rao et al, 1997), whereas, in the case of Bcl-2, interactions with mitochondrial outer membrane proteins (perhaps carnitine palmitoyltransferase I?) (Paumen et al, 1997) may be important.…”
Section: Predominant Localization To Intracellular Membranesmentioning
confidence: 99%
See 1 more Smart Citation